Methodology for the study of human nature in the works of Abu Hamid Al-Ghazali - Plojovic, Dzemal (International Institute of Islamic Thought and Civilization, Internationai Islamic University Malaysia, 2015)
This study focuses on al-Ghazali's methodology for the study of human nature. Its primary aim is to shed light on the scholar's methods by which one can get to know about the intricate subject matter of the nature of human being. There is no study that treats this particular aspect of the famous scholar's voluminous work even though a great deal of research has been conducted about similar topics, such as epistemology, psychology and the scholar's contribution to philosophy of science. Since the aim of this study is to restate al-Ghazali's methods, the main characteristic of the study is descriptive, and at times, comparative with the works of contemporary Muslim scholars. As al-Ghazali's methods are numerous and lay scattered in various parts of his work, the researcher has had to use analytical and synthetic procedures so as to present them in as systematic manner as possible. The findings of this study suggest that al-Ghazali used a great number of methods in his kalami, philosophical and sufī works. However, as it is attested by the scholar, the methods used by the Sufis had proven to be the most adequate ones to arrive at an understanding of human nature. Moreover, the findings are presented bearing in mind contemporary Muslim scholars' endeavor in the areas of philosophy of science and psychology.